Design and Construction of the Oil Palm Fruit Sorting Device Based on Color with PC Display - Tamba, Takdir (Journal of Technomaterial Physics, 2020)
This research discusses the design and construction of an oil palm fruit sorting tool and a counter for the number of oil palm fruits that work automatically using the working principle of a color sensor. This tool can work automatically because it is controlled by an ATmega328 microcontroller. Overall this system consists of designing a color sensor, motor controller, conveyor, and power supply. Item detection consists of 328 microcontroller technology, color sensor, proximity sensor, LCD, IOT, and PC display. The testing stages of this tool include testing the sensor circuit, testing the servo motor circuit, and testing the automatic oil palm fruit sorting and counting tool. When the oil palm fruit is detected, the color sensor will take data. The captured data will be sent to the microcontroller and displayed to the LCD, IOT and PC. There are additional devices in the form of undercooked, ripe and past ripe separation bars by utilizing a DC servo motor.ATmega328